Menguatkan Ikatan Sosial Antar Suku Dan Solusi Untuk Ketidakaktifan Remaja Desa Niur Dusun 02 Kecamatan Sukaraja - Aziza Aryati; Dera Buana Mirka; Annisa Ramdhani; Rehan Nur Kholis; Rado Ricardo; Siska Juniarti; Via Marlistina; Sadam Husin; Revika Revika; Ena Puspita; Aulia Hasanatul Aini (Pakis Journal Institute, 2024)
Indonesia is a country rich in ethnic, cultural and religious diversity, which is both a strength and a challenge in maintaining social balance. This diversity requires special efforts to build strong social ties, especially among teenagers as the nation's next generation. This research aims to identify the problem of adolescent inactivity in inter-ethnic social activities and offer solutions to strengthen these social ties. Using a qualitative approach with a case study method in Niur Village, this research found that lack of motivation and access to inter-ethnic activities as well as stigma and stereotypes were the main factors causing adolescent inactivity. To overcome this problem, multicultural education approaches and inclusive social programs that encourage positive interactions between ethnic groups have proven effective in increasing youth participation and strengthening social cohesion. The results of this research show the important role of education, social programs, and changing perspectives in society to create a generation of teenagers who are more active, tolerant, and contribute positively to social cohesion in Indonesia.